The Impacts of Ethical Action on Repurchase Intention Mediated By Customer Satisfaction on Online Business - Fitriningrum, Andriati; Ramadhan, Putra Novirwan (Zielona Góra: Faculty of Economics and Management Press)
This study aims to examine the impacts of ethical action taken by the company on customer satisfaction and intention to repurchase the products. The study was motivated by the emergence of unethical behaviour during online transactions due to limited direct contact between businesses and customers. Some companies have attempted to resolve these unethical issues.
Keywords: ethical action; trust; customer satisfaction; repurchase intention; e-commerce